Maternal Knowledge of Balanced Nutrition and Maternal Feeding Practices Associated with Stunting in Children Aged 24-60 Months in the Puskesmas Siempat Rube Working Area - Rina Elvrida Berutu; Risti Rosmiati; Esi Emilia; Nila Reswari Haryana; Fatma Tresno Ingtyas (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: The prevalence of stunting among children aged 24-60 months is a critical public health concern including in the Puskesmas Siempat Rube working area. Inadequate maternal knowledge about balanced nutrition and inappropriate feeding practices can contribute to the incidence of stunting. Objective: To analyze the relationship between maternal knowledge of balanced nutrition and maternal feeding practice on the incidence of stunting in children aged 24-60 months in the Puskesmas Siempat Rube working area. Method: This cross-sectional study was conducted in December 2023. The research sample consisted of 43 participants selected using purposive sampling. Balanced nutrition knowledge scores were categorized into poor, sufficient, and good; meanwhile, the higher the score for feeding practice, the better the mother's feeding practice was assumed. Height was assessed based on the TB/U indicator and categorized into stunting and not stunting. Hypotheses were analyzed using logistic regression tests, with statistical significance set at p < 0.05. Result: The prevalence of stunting in this study was 69.8%. Most mothers had insufficient knowledge of balanced nutrition (90.7%), and the average feeding practice score was 58.4. Maternal knowledge of balanced nutrition and maternal feeding practice are significantly related to the incidence of stunting in children aged 24-60 months in the Puskesmas Siempat Rube working area (p < 0.05). Maternal knowledge of balanced nutrition and maternal feeding practice act as protective factors against the incidence of stunting. The odds of children aged 24-60 months experiencing stunting were 0.056 times lower if their mothers had sufficient knowledge of balanced nutrition compared to mothers with poor knowledge. Similarly, each 1-point increase in a mother's feeding practice score could reduce the incidence of stunting by 0.910 times compared to mothers with a feeding practice score one point lower. Conclusion: Maternal knowledge of balanced nutrition and maternal feeding practice are significantly associated with the incidence of stunting in children aged 24-60 months in the Puskesmas Siempat Rube working area.